Pengaruh Penerapan Quality Control Data Radar Terhadap Akurasi Estimasi Curah Hujan Di Wilayah Pontianak Dan Sekitarnya - Mulya, Aditya; Lestari, Anisa Budi (JFT: Jurnal Fisika dan Terapannya, 2022)
Weather radar operational have a limitation that leads to a quality reduction of radar rainfall estimation, such as interference at Pontianak’s weather radar. The application of 3D Clutter Map and Data Processing (3DCDP), Brightband Echo Correction (BBC), and Z–Based Attenuation Correction (ZATC) which include in post–processing QC is the common procedure of radar limitation mitigation. This procedure applied to data of Pontianak weather radar over 1 January 2019 – 31 December 2019. The QC implemetation effect observed qualitatively and quantitatively by compare radar’s product before and after QC implementation. Data of radar rainfall estimation compared with rainfall observation data from AWS/ARG, and validated with RMSE and ME values. The comparison of the weather radar image shows that the interference and clutter around the weather radar is reduced. According to 19 validation value on the 10 cases of chosen rain, 18 value shows QC’s increased the accuracy of radar rainfall estimation, though insignificant and still underestimate.